Cadmium uptake and zinc-cadmium antagonism in Australian tropical rock oysters: Potential solutions for oyster aquaculture enterprises. Issue 1 (15th October 2017) - Munksgaard, Niels C.; Burchert, Shannon; Kaestli, Mirjam; Nowland, Samantha J.; O'Connor, Wayne; Gibb, Karen S.
Abstract: Variable and occasionally high concentrations of cadmium in wild oysters at a remote location with the potential to develop aquaculture enterprises motivated research into the distribution and sources of metals in oysters, seawater, sediment, suspended solids and phytoplankton. Saccostrea mytiloides and Saccostrea mordax contained cadmium concentrations exceeding the food standard maximum level (ML) at three of four sites. At one site with high zinc levels in sediment, oyster cadmium levels were below the ML. Metal levels in seawater were not correlated with cadmium levels in oysters but high cadmium/zinc ratios were measured in Trichodesmium erythraeum blooms. We suggest that oysters accumulate cadmium mainly from annual phytoplankton blooms except at sites where zinc availability is sufficiently high to prevent uptake though a mechanism of antagonistic exclusion. Knowledge of the source and uptake mechanisms of cadmium in oysters should lead to new management strategies to reduce cadmium levels in farmed oysters. Graphical abstract: Wild Blacklip Oyster from Northern Australia. Highlights: Tropical rock oyster aquaculture has potential as an Indigenous enterprise. Oysters accumulated Cd derived from annual phytoplankton blooms. Suspended Fe-oxides concentrated and transferred Cd to oysters. High Zn availability prevented Cd uptake by antagonistic exclusion at one site.